(untitled) (Research, Society and Development, 2024)
Introduction: Ventilatory asynchronies are an imbalance in coordination between the patient and the mechanical ventilator during assisted and controlled ventilation. This lack of synchrony occurs when the patient’s respiratory efforts are not in harmony with the ventilator’s operation or when the parameter settings are incorrect. Objective: To outline the profile of ventilatory asynchronies with greater occurrence in neurocritical care patients in an adult intensive care unit. Method: Pilot and observational study, through collection management of the TASY program and on-time results via B.I software. 47 adverse cases were analyzed, with a greater occurrence of asynchronies of insufficient flow and double triggers. Results: Early cycling and excessive flow 1%, ineffective triggering and late cycling approximately 3%, reverse triggering 7%, self-triggering 8%, insufficient flow 28% and double triggering 48%. Conclusion: It is concluded that the mechanical changes with the greatest occurrence are asynchronies of insufficient flow and double shots, with a prior future need to propose control and training measures, such as the improvement of active ventilation monitoring, as both have a classification standard relates the patient’s participatory activity. In this way, intelligence technology software management was effective in profiling the asynchronies evaluated here.